What Happened to Indonesia SOES Governance? - M. , Alan Jayaatmaja; Rachmawati, Rima; Haizam Mohd Saudi, Mohd (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine the relationship between internal audit, audit committee, and internal control systems in SOEs. The background of this research is an indication of a decline in SOES performance due to the high number of SOES officials who are corrupt. The weak internal control is indicated by the weak role of the internal audit and the audit committee in maintaining SOES internal control. The study was conducted at a state-owned SOES headquartered in Bandung. The results of the study stated that there was evidence that internal audit and audit committee influence the effectiveness of SOES internal control, with the amount of control variability in the form of internal audit and audit committee variability of 61.6%.